Consensus Control of Second-Order Multiagent Systems with Particle Swarm Optimization Algorithm - Xiongfeng Deng; Xiuxia Sun; Ri Liu; Shuguang Liu (Journal of Control Science and Engineering)
This paper considers the consensus problem of second-order multiagent systems. Firstly, an improved consensus control protocol is proposed. Then, the convergence of the proposed control protocol is analyzed by applying Lyapunov stability theory. In order to improve the control effect of a given system, the particle swarm optimization (PSO) algorithm is introduced and an improved PSO algorithm is proposed. Additionally, a mapping relationship with agents and the individuals of PSO algorithm is designed. Finally, two simulation examples are provided to illustrate the effectiveness of proposed control protocol and the control effect of PSO algorithm.